Selective Targeting of the L858R Mutation (EGFR) in Non-Small Cell Lung Cancer: A Mechanism for Advancing Targeted Chemotherapy - Arora, Rohan; Krishnan, Venkat (Frontiers in Oncology, 2017)
Lung cancer remains one of today's most deadly and intractable cancers. Non-Small Cell Lung Cancer (NSCLC) accounts for roughly 85% of lung cancers, with an extremely poor survival rate. To ensure patient comfort and survival the development of a selective therapy is imperative. However, Lung Cancer does not display surface proteins associated uniquely with tumor cells; thus it is very difficult to develop a tumor-specific drug. Current techniques that target over-expression of proteins or inhibit growth pathways are either non-specific or prone to rapid drug resistance. The goal was to design a drug targeted to structural mutations expressed by tumor-associated general surface proteins, thereby combating the lack of tumor-unique markers in Lung Cancer. Mutant-EGFR was identified as a potential target due to its prominence in tumor cells. Due to their size, it was determined that Small Molecules would be most effective at targeting isolated changes in protein structure, and thereby differentiating between the tumor-associated mutant-EGFR and the healthy wild type. Conformational analysis of a virtual binding study conducted in VINA predicted a set of drug-like small molecules specific for the L858R mutation in EGFR. One molecule (ZN47) was then acquired and conjugated to a carrier protein to form a multifaceted happen-protein conjugate. Multiple ELISAs were conducted to confirm the specificity of the conjugate to both tumor-associated mutant EGFRs. The results indicate that the identified molecule may be highly selective for tumor associated L858R-EGFR, but further research, including a complete dosage binding study, is necessary for full validation.